2015
DOI: 10.3109/09638288.2015.1061612
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of parents enabling participation of their child with a physical disability at home, at school and in the community

Abstract: In-depth exploration and understanding of parents' articulated matters must be shared and taken seriously by policymakers and service providers. Parents' knowledge and experiences should be of major relevance to improve paediatric rehabilitation and other services for children with a physical disability. Implications for Rehabilitation To achieve tailored pediatric rehabilitation, involvement and needs of parents in enhancing their child's participation ought to be acknowledged. Active use of parents' experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Moreover, the present study illustrates that when support systems do not meet the parents' needs, they take on a role as activist to fight for their children's right to PA. Other researchers have made the same description of parents fighting to get appropriate help and aids for their children (Piskur et al 2016;Schleien et al 2014;Woodgate et al 2015). The role as activist was described in this present study as an energy thief for the parents due to the lack of support systems.…”
Section: Interpretation Of the Four Rolesmentioning
confidence: 55%
“…Moreover, the present study illustrates that when support systems do not meet the parents' needs, they take on a role as activist to fight for their children's right to PA. Other researchers have made the same description of parents fighting to get appropriate help and aids for their children (Piskur et al 2016;Schleien et al 2014;Woodgate et al 2015). The role as activist was described in this present study as an energy thief for the parents due to the lack of support systems.…”
Section: Interpretation Of the Four Rolesmentioning
confidence: 55%
“…The majority of items (23 items) were society level items. Several studies have also reported that unsuitable environments and attitudes and behaviours of the general public limited the participation of children with disabilities and their families [3,4,6,8,21]. Furthermore, all the items established in the required assistance and resources domain required society level improvement (#35-39).…”
Section: Discussionmentioning
confidence: 99%
“…The built environment was recognised as the most frequent barrier towards achieving participation in the community whilst assistive technology, environmental adaptations, and facilities were determined the top three factors that enhance participation of their child. In a second small qualitative study, Piškur et al (2015b) interviewed 13 parents of children with a disability to explore the lived experiences of enabling participation for their child. The notion that reduced participation results from restricted environments is reinforced (Piškur et al, 2015a;Piškur et al, 2015b;Raymond et al, 2014), particularly environments such as sanitary facilities, entrances, and stairs within both the school and in the broader community (Piškur et al, 2015b).…”
mentioning
confidence: 99%
“…In a second small qualitative study, Piškur et al (2015b) interviewed 13 parents of children with a disability to explore the lived experiences of enabling participation for their child. The notion that reduced participation results from restricted environments is reinforced (Piškur et al, 2015a;Piškur et al, 2015b;Raymond et al, 2014), particularly environments such as sanitary facilities, entrances, and stairs within both the school and in the broader community (Piškur et al, 2015b). Similarly in Australia, Bigby and Balandin's (2005) mixed methods study purposively sought 40 Victorian day and community services accessed by individuals with lifelong disabilities.…”
mentioning
confidence: 99%